High-throughput analysis of polyethoxylated tallow amine homologs in citrus using a modified QuEChERS-HILIC-MS method - Li, Minjie; Wang, Hongping; Li, Simeng; Chen, Xueying; Jin, Maojun; Shao, Hua; Wang, Jing; Jin, Fen (Frontiers in Nutrition, 2022)
A new method is described based on ultraperformance liquid chromatography (UPLC) with electrospray mass spectrometry detection for comprehensive quantitative analysis of 66 polyethoxylated tallow amines (POE-Tallowamine) homologs in citrus. Efficient separation, reduced band broadening, and high sensitivity were achieved by employing a acetonitrile-aqueous solution containing 10 mM ammonium formate gradient on a HILIC column with a modified QuEChERS method. Quantitative accuracy and precision of the method were improved by the use of matrix-matched calibration standards. The average recoveries of the POE-Tallowamine homologs at different spiked concentrations ranged from 71.9 to 112%, with RSDs < 16.6%. The limits of detection (LODs) and limits of quantification (LOQs) for POE-Tallowamine homologs were 0.01–2.57 and 0.03–8.58 μg/kg, respectively. The method was successfully applied to determine POE-Tallowamine in citrus samples from Chinese typical regions in 2021. The POE-Tallowamine was detected in all 54 samples, and the highest concentration (143 μg/kg) of POE-Tallowamine was found in Jelly orange from Zhejiang province.